PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR - Ayu Kusuma; Desy Ismah Anggraini (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This study aims to examine and analyze the effect of green accounting as a proxy for environmental costs and environmental performance on profitability. The object of research used is a consumer goods industrial manufacturing company listed on the Indonesia Stock Exchange. The data collection method is based on the company's annual report published by the Indonesia Stock Exchange. The collection of samples using purposive sampling. The number of samples is 12 consumer goods industrial manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020. Data analysis was carried out using SPSS 24. Based on the results of partial testing (T test) the environmental cost variable has no effect on profitability, the environmental performance variable has no effect to profitability. Based on the results of the simulation test (F test) environmental costs and environmental performance together have no effect on profitability.